SOSIALISASI DAN PEMBUATAN PUPUK ORGANIK CAIR DARI SERABUT KELAPA - Hidayat, Diky; Mahasiswa KKN Univeristas Lampung (BUGUH: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2025)
Liquid organic fertilizer (POC) is a fertilizer that is available in liquid form, POC can be interpreted as fertilizer that is made naturally through a fermentation process so as to produce a solution resulting from decay from plant residues, as well as animal or human waste. In this case, the material used is coconut fibers. This article contains an overview and explanation related to the socialization work program and the manufacture of liquid organic fertilizer made from coconut fibers. The writing of this article uses a qualitative approach with a descriptive-qualitative model. Overview and explanation related to the work program of making compost, including the process, stages, results, and benefits. The writing of this article uses a qualitative approach with a descriptive-explanatory model. As a result, the community receives new understandings and insights in terms of household waste utilization. In addition, the community can reduce the use of chemical fertilizers and factory-made fertilizers that are generally already used by rural communities, so as to minimize the expenditure of village farming communities in the process of farming. This article is limited to the implementation of KKN Kerbang Dalam Period 1 2023.